Assessing Post-Stroke Behavior in Mouse Models of Focal Ischemia. Issue 3 (March 2013) - Balkaya, Mustafa; Kröber, Jan M; Rex, Andre; Endres, Matthias
Experimental treatment strategies and neuroprotective drugs that showed therapeutic promise in animal models of stroke have failed to produce beneficial effects in human stroke patients. The difficulty in translating preclinical findings to humans represents a major challenge in cerebrovascular research. The reasons behind this translational road block might be explained by a number of factors, including poor quality control in various stages of the research process, the validity of experimental stroke models, and differences in drug administration and pharmacokinetics. Another major difference between animal studies and clinical trials is the choice of end point or outcome measures. Here, we discuss the necessity of poststroke behavioral testing to bridge the gap between clinical and experimental end points. We review established sensory-motor tests for outcome determination after focal ischemia based on the published literature as well as our own personal experience. Selected tests are described in more detail and good laboratory practice standards for behavioral testing are discussed. This review is intended for stroke researchers planning to use behavioral testing in mice.